Detection of genetic variations using RAPD markers in Siberian huskies affected with swimming puppy syndrome - Chomdej,S. (Chulalongkorn University, 2015)
Swimming puppy syndrome (SPS) is a curious disease found in dogs. The causes and pathology of this disease are still unknown, although heredity is usually considered to be one of the underlying factors. The objective of this study was to investigate the association between genetics and SPS in a Siberian husky model. Four Siberian husky puppies diagnosed with SPS were subjects of this study, while three other healthy Siberian husky puppies served as controls. Blood samples were collected for DNA isolation, using random amplified polymorphic DNA (RAPD) technique with 16 random primers. No genetic variation was found between affected puppies and healthy puppies, which indicated that swimming puppy syndrome is not controlled by genetics.